Development of isohyet map using inverse distance weighting and ordinary kriging methods for Klang River basin - Lee, Pik Jun (2018)
Klang river basin is one of the most important basins in Selangor. It covers federal territory of Kuala Lumpur, Hulu Langat, Gombak, Petaling and Klang. This basin experiences the highest economic development in Malaysia. Therefore, appropriate knowledge of rainfall distribution in this basin is very useful for disaster management and water resource management. Spatial interpolation method is a frequent common method to find the estimate values of meteorological parameters. In this study, the rainfall data were classified into monthly and annually average rainfall (before and after 2000) in order to assess the rainfall patterns in the river basin. The isohyet maps were produced using Inverse Distance Weighting (IDW) and Ordinary Kriging (OK) through ArcGIS Geostatistical Analyst. These methods are compared and evaluated using cross validation. From the analysis, Ordinary Kriging (OK) is the most optimum interpolation method over Klang river basin because it has less variation of estimate values, smaller error and greater central tendencies. The isohyet maps generated by Ordinary Kriging then are used to analyze the impact of climate change over this basin. It can be observed that annually average rainfall in this basin had been increased after 20 century. The driest area is found in Klang, Selangor which located at the lowest part of the catchment. The average rainfall had been decreased compare to previous due to global warming effect. The study area becoming hotter and make drought more severe. Meanwhile, the wettest area is located in Kuala Lumpur. Kuala Lumpur is in the middle part of the catchment. The average rainfall had been increased intensely in the city. This is because of the urban heat island effect that results in higher temperature in the city. Consequently, flash flood events may occur after two to three hours of heavy rain in this region.